Z ducha muzyki? Czternaście wariacji o Mieście: partyturze i innych „wierszach nadsłownych” Mariana Grześczaka - Bogalecki, Piotr (Przestrzenie Teorii, 2019)
The article covers wiersze-nadsłowne [“supra-verbal” poems] by Marian Grześczak written in the period of 1959–1963, which was one of the first specimens of concrete poetry in Poland. The main part comprises an elaborate analysis of a work titled Miasto: partytura [City: score] (previously called: Miasto, parodia [City, parody]). The text becomes a springboard for the presentation of original literary theoretical ideas concerning the links between the literary text and musical notation, and in doing so refers to the findings of authors such as G. Agamben and J. Derrida, as well as G. Deleuze and F. Guattari, but predominantly to Grześczak’s own commentaries, as one of the first Polish commentators of the international concrete poetry movement. The article also mentions sixteen unpublished poems, which were found in an archive of visual poems by Grześczak, whose analysis provides a basis for rejecting the notion pervading relevant literature of the “sporadic” and “insignificant” character of the poet’s concrete works. Thus, the article is an attempt at literary historical revision and a contribution to the re-interpretation of the history of concrete and experimental poetry in Poland.